PERANCANGAN KOMUNIKASI VISUAL PENGENALAN TOKOH PERJUANGAN KEMERDEKAAN SUMATERA SELATAN TERHADAP MASYARAKAT KOTA PALEMBANG - Darmawan, Adel Ari; Yulius, Yosef; Iswandi, Heri (AMARASI: JURNAL DESAIN KOMUNIKASI VISUAL, 2024)
South Sumatra is one of the provinces in Indonesia which has various stories behind its independence, one of which is the services of the South Sumatran freedom fighters. There were several freedom fighters from South Sumatra, such as Sultan Mahmud Badaruddin II, A.K Gani, A.M Thalib, Captain A. Rivai, Col. H Barlian, Harun Sohar, Hasan Kasim, Bambang Utoyo, Abdul Rozak and Dr. Mass. of the many figures of the South Sumatran Independence Fighters, there are very rarely fragments of stories that introduce these fighters. This is due to the very limited media that help introduce the South Sumatra independence fighters such as children's books that tell information about fighters and fragments of the stories of South Sumatran fighters. the community is no longer bound by offline media such as books and so on and the lack of interest from the public to get to know these South Sumatran independence fighters is due to the lack of interesting media for the public to see. Therefore, it is necessary to design visual communication to introduce South Sumatran independence fighters to the people of Palembang city so that it can become a medium for introducing the various stories and figures behind independence in South Sumatra, especially in the city of Palembang. So that the identity of the figures of the South Sumatran freedom fighters is not lost and forgotten and awakens a sense of pride and nationalism for the people of South Sumatra.